2001
DOI: 10.1046/j.0007-1323.2001.01918.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of a mediastinal leak following radical oesophagectomy

Abstract: Routine postoperative contrast radiology cannot be recommended. On clinical suspicion of a leak patients require both contrast radiology and endoscopic evaluation. Isolated anastomotic leaks can be managed successfully with non-operative treatment, whereas more extensive leaks from the gastric conduit require revisional surgery which carries a high mortality rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
122
0
10

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 172 publications
(137 citation statements)
references
References 7 publications
4
122
0
10
Order By: Relevance
“…Interestingly, although available studies showed that patients do not benefit from RRCS on POD 7 [16-19], between days 5 and 8 [20] or within the first postoperative week [21], only scarce data are available on the typical time point of occurrence of AL after esophagectomy. Therefore, we investigated the typical time point of occurrence of AL to evaluate if RRCS could be useful at different time points following esophagectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, although available studies showed that patients do not benefit from RRCS on POD 7 [16-19], between days 5 and 8 [20] or within the first postoperative week [21], only scarce data are available on the typical time point of occurrence of AL after esophagectomy. Therefore, we investigated the typical time point of occurrence of AL to evaluate if RRCS could be useful at different time points following esophagectomy.…”
Section: Discussionmentioning
confidence: 99%
“…1,2) The causes of post-operative esophageal perforation are multifactorial, and the perforation sites are the anastomosis site and the gastric conduit. 2) Clinical presentation can be divided into early fulminant, clinically silent and clinically apparent leakages.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Surgical treatment is preferred for early fulminant leakage due to partial or total necrosis of the conduit and non-surgical sealing attempts could be performed for clinically apparent post-operative anastomotic leakage. Kiev et al reported palliative management using an endoscopic PolyFlex stent for patients with mid-to distal esophageal perforations without mediastinitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations